Camel's Analysis of Banking Financial Performance Listed on The IDX - Nur Aini, Sinta; Takarini, Nurjanti (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Financial performance analysis aims to assess the effectiveness and efficiency of a company's financial management. This study aims to measure the influence of the CAMEL (Capital, Asset Quality, Management, Earning, and Liquidity) variables on the bank's financial performance, which is measured using return on assets (ROA). The method applied in this study is a quantitative approach with multiple linear regression. This study examines the relationship between the independent variable of CAMEL and the dependent variable of financial performance (ROA). The data used is secondary data in the form of annual financial statements from banks listed on the Indonesia Stock Exchange (IDX) for the period 2020 to 2023. The results of the study show that asset quality, liquidity, and capital have no effect on the financial performance of banks, while management and income have a significant influence.